2008
DOI: 10.1186/1743-7075-5-11
|View full text |Cite
|
Sign up to set email alerts
|

Minimal nutrition intervention with high-protein/low-carbohydrate and low-fat, nutrient-dense food supplement improves body composition and exercise benefits in overweight adults: A randomized controlled trial

Abstract: Background: Exercise and high-protein/reduced-carbohydrate and -fat diets have each been shown separately, or in combination with an energy-restricted diet to improve body composition and health in sedentary, overweight (BMI > 25) adults. The current study, instead, examined the physiological response to 10 weeks of combined aerobic and resistance exercise (EX) versus exercise + minimal nutrition intervention designed to alter the macronutrient profile, in the absence of energy restriction, using a commerciall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 41 publications
2
32
0
Order By: Relevance
“…Multiple studies in this review (Table 3) showed 0.8-3.3 g/kg/day greater fat loss in higher protein participants over 4–26 wk when change from habitual intake was 20.2%-35.3% [11,32,38,43]. There appeared to be three outliers in Table 3[22,33,35].…”
Section: Discussionmentioning
confidence: 92%
“…Multiple studies in this review (Table 3) showed 0.8-3.3 g/kg/day greater fat loss in higher protein participants over 4–26 wk when change from habitual intake was 20.2%-35.3% [11,32,38,43]. There appeared to be three outliers in Table 3[22,33,35].…”
Section: Discussionmentioning
confidence: 92%
“…While much research has been conducted highlighting the benefits of even modest amounts of physical activity, a small number of studies have reported upon the impact of an exercise program with various dietary interventions of which can include caloric restriction and alterations in the ratio of dietary protein and dietary carbohydrate [3,4,22,23]. Furthermore, even less scientific literature has reported upon physiological as well as biochemical adaptations that occur following this type of dieting in combination with resistance-based exercise [3,22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, although some studies suggest that consuming thermogenic supplements are beneficial in catalyzing weight loss in previously sedentary, overweight individuals (3,24), partaking in a structured exercise regimen with added protein intake may provide a satisfactory impetus for favorably altering body composition and fitness parameters as we are reporting in the present investigation. In light of this, Kerksick et al reported this outcome in a 14-week study involving a 3 dÁwk 21 exercise program with carbohydrate restricted diets (14), whereas Lockwood et al (18) have suggested that ad libitum addition of a meal replacement may be a satisfactory stimulus for energy intake reduction and weight loss. As such, no clear consensus has been made regarding the potential synergistic impact of added macronutrient intake and regular exercise in previously sedentary, overweight individuals (26).…”
Section: Discussionmentioning
confidence: 96%
“…Researchers have employed such a strategy by manipulating macronutrient percentages in assigned diets (17) or by providing study subjects undergoing chronic resistance and cardiovascular exercise a daily meal-replacement product (18), both of which increased overall protein intake in a subset of the subjects, to positively affect body composition, performance measures, and clinical safety markers. Based on the above data regarding thermogenic ingredients and dietary protein manipulation, the potential exists for a thermogenic product, in conjunction with a diet supplemented with protein and concurrent exercise, to positively impact body composition and clinical safety markers.…”
Section: Introductionmentioning
confidence: 99%